1996
DOI: 10.3109/02656739609023688
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative thermochemotherapy of oral cancer using magnetic induction hyperthermia (Implant Heating System: IHS)

Abstract: Eight patients with primary cancer of the oral cavity were preoperatively treated by combined treatment with hyperthermia and chemotherapy. They received two courses of chemotherapy, which included intra-arterial infusion of 100 mg of cisplatin (CDDP) and 25 mg of peplomycin (PEP) via the superficial temporal artery. The patients also received interstitial hyperthermia for 45 min once a week using the Implant Heating System (IHS) with chemotherapy. IHS consists of ferromagnetic implant, induction coil and gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Table I summarizes the characteristics of resonant circuits with various combinations of the inductor and the capacitor. It is noted that a lower residual resistance and a larger electromotive force of the inductor are essential for a higher temperature rise of the circuits from the maximum consumed power described in (1). A larger electromotive force is induced in a coil of larger inductance.…”
Section: Dependence Of Diameter Of Coil Wirementioning
confidence: 99%
See 1 more Smart Citation
“…Table I summarizes the characteristics of resonant circuits with various combinations of the inductor and the capacitor. It is noted that a lower residual resistance and a larger electromotive force of the inductor are essential for a higher temperature rise of the circuits from the maximum consumed power described in (1). A larger electromotive force is induced in a coil of larger inductance.…”
Section: Dependence Of Diameter Of Coil Wirementioning
confidence: 99%
“…It has been known that the survival rate of cancer cells drops sharply at 42.5 • C. In addition, the temperature of the cancerous tissue rises more easily than that of normal tissues because of poor cooling by a sluggish blood flow. Hyperthermia elevates the local temperature above 42.5 • C to kill cancer cells, whereas most of the surrounding normal tissues are not damaged at the temperatures below 44 • C. The hyperthermia using implants has been reported in terms of its ability to control the temperature of cancerous tissues, and a possibility to warm them locally [1,2]. A resonant circuit, which is heated efficiently by an external magnetic field, is one of the candidates for the implants [3].…”
Section: Introductionmentioning
confidence: 99%
“…And, hyperthermia combined with chemotherapy also has bettered clinical response for patients with head and neck cancers. Tohnai et al [ 55 , 56 ] reported that eight patients with primary cancer of the oral cavity were preoperatively treated by combined treatment with hyperthermia and chemotherapy. As a result, CR was observed in seven patients and partial response (PR) in one, and postoperative pathological examination showed no residual tumor cells in any specimen.…”
Section: Clinical Application Of Local Hyperthermia In Head and Neck mentioning
confidence: 99%
“…The implants of tiny elements inside of the body are heated up by an external energy source. A combination of magnetic materials as the implants and a magnetic field applied from outside of the body has attracted much attention [1,2]. Recently fundamental research using magnetic nanoparticles has been also popular [3].…”
mentioning
confidence: 99%